Liolaemus grosseorum: Diet - Brizio, María Victoria (2019)
Liolaemus grosseorum is amember of the boulengeri group of Liolaemus and is an oviparousand insectivorous mid-sized lizard (max SVL = 55 mm;Etheridge 2001. Cuad. Herpetol. 15:3?15). It is distributed in fourof Argentina?s provinces: Mendoza, La Pampa, Neuquén, and RíoNegro (Pérez et al. 2018. Cuad. Herpetol. 32:141?143). There arefew studies on the ecology and natural history of this species,including its diet. Here we report L. grosseorum preying upona scorpion, Timogenes mapuche. At 0900 h on 27 January 2019,during a sampling campaign in the Bajo de Añelo, NeuquénProvince, Argentina (38.3481°S, 69.1031°W, WGS 84; 344 m elev.),we found an adult male L. grosseorum preying on a scorpion (52mm long) for ca. 5 min, until he ate it completely (Fig. 1). Scorpionsare usually nocturnal animals in the Monte landscapes andL. grosseorum is a diurnal, mostly sit and wait predator, thereforeit is likely these encounters are rare.